Optimasi Waktu Tunggu Lampu Lalu Lintas dengan Mengaplikasikan Teori Graf dan Metode Webster - Ezra Shalom Sendow; Murni Sulistyaningsih; Jorry F. Monoarfa (Departement of Mathematics Education, 2023)
Mobility in the city of Manado is a trigger for the occurrence of traffic volume density, leading to congestion at several points, particularly at intersections. The Toar-Lumimuut intersection is one such vulnerable location where congestion often occurs, despite the presence of traffic lights controlling the flow of vehicles. In fact, many drivers still have to wait for the red light more than once at the Toar-Lumimuut intersection. Based on these findings, it indicates that the waiting time for traffic lights at the Toar-Lumimuut intersection is still inefficient. This study aims to determine the synchronized waiting time for traffic lights according to the traffic situation, in order to achieve a more optimal waiting time for traffic lights. This problem can be addressed using graph theory and the Webster method. The research yielded results, with the optimum cycle time increasing to 285 seconds, accompanied by an increase in green light duration and a decrease in red light duration as a percentage for each road segment. Therefore, the research concludes that this provides a more effective waiting duration.